2009
DOI: 10.1016/j.jhazmat.2008.10.114
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phosphate from aqueous solution by red mud using a factorial design

Abstract: a b s t r a c tThe purpose of the work is to study the adsorption of phosphate on red mud from aqueous solutions using 2 3 full factorial designs. The important parameters, which affect the removal efficiency of phosphate and final pH of solution (pH f ), such as phosphate concentration, initial pH of solution (pH i ) and the red mud dosage were investigated. The effects of individual variables and their interaction effects for dependent variables, namely, phosphate removal efficiency and pH f were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 36 publications
2
57
0
1
Order By: Relevance
“…The average chemical composition of RM was listed in Table 1, RM is mainly consisted of Ca, Si, Fe and Al oxides. The single-point N 2 -BET method indicated that the specific surface area of a typical RM sample was about 14.76 m 2 g −1 [18].…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…The average chemical composition of RM was listed in Table 1, RM is mainly consisted of Ca, Si, Fe and Al oxides. The single-point N 2 -BET method indicated that the specific surface area of a typical RM sample was about 14.76 m 2 g −1 [18].…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Previous studies have shown that the adsorption capacity of the phosphorus exists in many lowcost sorbents, such as fly ash [13], bentonite, natural zeolite, alum sludge [14], red mud [15][16][17][18], and other waste materials [19]. Red mud (RM) is a waste residue formed after the caustic digestion of bauxite during the production of alumina.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Different types of low-cost, high-capacity materials have long been used to remove phosphate, such as granulated coal ash (Asaoka and Yamamoto, 2010), red mud Zhao et al, 2009;Yue et al, 2010) and lanthanum-doped vesuvianite (Li et al, 2009). Researchers have investigated ferric manganese oxide as an adsorbent for phosphate and arsenic removal .…”
Section: Phosphate Removal Using Novel Combinedmentioning
confidence: 99%